Veränderung der Patientenklientel mit hüftgelenknahen Femurfrakturen in der letzten Dekade: Inzidenz, Alter, Nebenerkrankungen und Liegezeiten = Changes in the patient population with proximal femur fractures over the last decade : incidence, age, comorbidities, and length of stay - Muhm, Markus Joachim; Ruffing, Thomas (Der Unfallchirurg, 2018)
Background: Over the last decade, the percentage of people >65 years has increased from 16.6% to 20.7%. In industrialized countries, the annual incidence in people >65 years with a proximal femur fracture is about 600-900 per 100,000 population. The incidence will increase by 3-5% per year. Guidelines advocate early surgery as soon as possible but within 24 h. External quality control requires surgical treatment within 48 h. In this study, the changes in the patient population with proximal femur fractures and their treatment during the last decade were investigated. Methods: From 2005-2014, data of all patients ≥65 years with proximal femur fractures were recorded. The patients were treated in a level 1 trauma center certified by the German Society for Trauma Surgery. The evaluation was carried out by means of descriptive statistics. Results: In all, 2093 patients with proximal femur fractures (1164 trochanteric neck fractures and 929 femoral neck fractures) were evaluated. The annual increase in the percentage of patients was 1.5-2%. Over the decade, the percentage of patients increased by 20% and the average age increased by 2 years. There were no changes in comorbidities or case mix index during the investigation period. Despite the increase of the preoperative waiting times, a decrease in the total length of stay was found. Discussion: The increase in the number of patients, as well as the requirements of the guidelines and external quality control are relevant challenges for the hospitals. More human and material resources (e. g., surgical capacity) are needed. The increase in the age of the patients, their comorbidities, and medication must be taken into account, e. g., in the context of geriatric orthopedic trauma centers.
Gesehen am 27.05.2019
Online publiziert: 20. Oktober 2017